Unilateral Sacral Fractures Demonstrate Slow Recovery of Patient-Reported Outcomes Irrespective of Treatment. Issue 4 (April 2022) - Mullis, Brian H.; Agel, Julie; Jones, Clifford; Lowe, Jason; Vallier, Heather; Teague, David; Kempton, Laurence; Schmidt, Andrew; Friess, Darin; Morshed, Saam; Miller, Anna N.; Leighton, Ross; et al.
Abstract : Supplemental Digital Content is Available in the Text. Abstract : Objectives: To report functional outcomes of unilateral sacral fractures treated both operatively and nonoperatively. Design: Prospective, multicenter, observational study. Setting: Sixteen Level 1 trauma centers. Patients/Participants: Skeletally mature patients with unilateral zone 1 or 2 sacral fractures categorized as displaced nonoperative (DN), displaced operative (DO), nondisplaced nonoperative (NN), and nondisplaced operative (NO). Main Outcome Measurements: Pelvic displacement was documented on injury plain radiographs. Short Musculoskeletal Function Assessment (SMFA) scores were obtained at baseline and at 3, 6, 12, and 24 months after injury. Displacement was defined as greater than 5 mm in any plane at the time of injury. Results: Two hundred eighty-six patients with unilateral sacral fractures were initially enrolled, with a mean age of 40 years and mean injury severity score of 16. One hundred twenty-three patients completed the 2-year follow-up as follows: 29 DN, 30 DO, 47 NN, and 17 NO with 56% loss to follow-up at 2 years. Highest dysfunction was seen at 3 months for all groups with mean SMFA dysfunction scores: 25 DN, 28 DO, 27 NN, and 31 NO. The mean SMFA scores at 2 years for all groups were 13 DN, 12 DO, 17 NN, and 17 NO. Conclusions: All groups (operative/nonoperative and displaced/nondisplaced) reported worst function 3 months after injury, and all but (DN) continued to recover for 2 years after injury, with peak recovery for DN seen at 1 year. No functional benefit was seen with operative intervention for either displaced or nondisplaced injuries at any time point. Level of Evidence: Prognostic Level II. See Instructions for Authors for a complete description of levels of evidence.